Mini review: Ethnopharmacology and phytochemistry of the tropical American family Marcgraviaceae - Carballo-Arce, Ana Francis; Villegas-Peñaranda, Luis Roberto; Garro-Álvarez, Raúl Esteban; Alfaro-Ureña, Yohana; Sandoval-Barrantes, Manuel; Mullally, Martha; Arnason, John Thor (Frontiers in Pharmacology, 2025)
The Marcgraviaceae is a neotropical family of lianas and shrubs that has received limited investigation for its medicinal properties. Characterized by prominent, nectar-rich terminal inflorescences, the family comprises 7 genera and 136 species. Traditional uses among Indigenous communities in the Americas include treatments for anxiety, sleep disorders, mental health conditions, and various dermatological ailments. Pharmacological and phytochemical studies have confirmed that extracts from the genus Marcgravia, traditionally used for dermatological conditions, inhibit bacterial quorum sensing, with active principles identified as naphthoquinones. Schwartzia brasilensis (syn. Norantea brasilensis) has demonstrated antiviral activity against Dengue virus, in vivo antimalarial efficacy, anti-inflammatory properties, and DNA-protective effects, but active principles remain to be accurately determined. Ruyschia phylladenia, containing triterpenes and isofraxidin, has shown promising antileishmanial, antibacterial, and antitumor activities. Pharmacological research on Souroubea spp. from Central America has revealed strong anxiolytic properties in animal models, with active compounds identified as the triterpenes betulinic acid, α-amyrin, and β-amyrin. Following toxicity and efficacy trials, Souroubea sympetala leaf extracts have been developed into a practical veterinary formulation for the management of noise aversion in dogs. Given the extensive diversity and wide distribution of this tropical American family, Marcgraviaceae offers considerable untapped potential for the discovery of new medicinal properties and phytochemicals.